ajutooooor :) va rog
Anexe:
Răspunsuri la întrebare
Răspuns de
1
(13rad3/6 - 5rad3/3) - (2rad2/3 - 6rad2/5 + 5rad2/4 - 23rad2/60) =
(13rad3 - 10rad3)/6 - (40rad2 - 72rad2 + 75rad2 - 23rad2) =
3rad3/6 - 20rad2/60 =
rad3/2 - rad2/3 =
(3rad2 - 2rad3)/6
(13rad3 - 10rad3)/6 - (40rad2 - 72rad2 + 75rad2 - 23rad2) =
3rad3/6 - 20rad2/60 =
rad3/2 - rad2/3 =
(3rad2 - 2rad3)/6
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba rusă,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă